Wearable fabric supercapacitors based on CNTs and polyhedral ZnO with a wide potential window - Samuel, Edmund; Joshi, Bhavana; Park, Chanwoo; Aldalbahi, Ali; El-Newehy, Mohamed; Lee, Hae-Seok; Yoon, Sam S. (International Journal of Energy Research, 2022)
Wearable electronic devices such as health monitors, sensors, and e-skin can be powered by lightweight, high-power supercapacitors. Using a binder-free and low-temperature hydrothermal method, polyhedral ZnO nanoparticles were grown on carbon nanotube (CNT)-decorated cotton fabric, which is friendly to human skin and highly wearable, inexpensive, and thus commercially viable. The concentration of the starting material, zinc acetate, was varied to optimize the electrochemical performance. The evenly spaced polyhedral ZnO facilitated efficient permeation of the electrolyte into the active material. The fabric filaments were decorated with CNTs to enhance electron transfer and the overall electrochemical processes. The symmetric cell comprised of cotton fabric decorated with ZnO polyhedron/CNT showed no discernible change in the cyclic voltammetry curves even after 500 bending cycles, demonstrating the mechanical durability of the electrode. The potential window of 1.6 V using a Na2SO4/K2SO4 aqueous dual-ion electrolyte improved the long-term electrochemical stability and increased the energy storage capacity. The capacitance retention was 94% after 5000 cycles at a current density of 1 A center dot g(-1), indicating long-term electrochemical stability. A specific capacitance of 375 F center dot g(-1) at a current density of 5 A center dot g(-1) and energy density of 33.3 Wh center dot kg(-1) at a power density of 2000 W center dot kg(-1) were recorded for the optimized electrode. Highlights Polyhedral ZnO was grown on cotton fabric using a hydrothermal process. The electrochemical performance was optimized by varying the zinc acetate concentration. The highest specific capacitance was 375 F center dot g(-1) at a current density of 5 A center dot g(-1). Under optimal conditions, the capacitance retention was 94% at N = 5000 cycles. The energy density of the electrode was as high as 33.3 Wh center dot kg(-1).
Keywords: carbon nanotube; Cotton fabric; hydrothermal process; wearable supercapacitor; ZnO polyhedron